Is Coronal Restoration a Predictor of Posttreatment Apical Periodontitis? - Persic Bukmir, Romana; Paljevic, Ema; Vidas, Jelena; Glazar, Irena; Pezelj-Ribaric, Sonja; Brekalo Prso, Ivana (European Journal of Dentistry, 2021)
Objectives To investigate the posttreatment apical periodontitis (AP) in endodontically treated teeth through a multivariate approach and to analyze the relative importance of quality and type of coronal restoration as predictors of periapical disease.Materials and Methods The present study sample was drawn within 2-year period from the 1,072 consecutive patients older than 18 years, first time attending the Dental Clinic of the Clinical Hospital Center Rijeka, Croatia. A total of 1,350 endodontically treated teeth were included in the study. For each tooth, the periapical status, root filling quality, intracanal post, separated file presence, marginal bone loss, and quality and type of coronal restoration were recorded.Statistical Analysis Chi-square tests were used to analyze the variations in the periapical status, quality of root canal filling, and quality of coronal restoration in different tooth types. The effect of explanatory variables on periapical status was explored using univariate and multivariate logistic regression models. The outcome variable was set as the presence versus absence of AP in the tooth.Results Multivariate logistic regression analysis revealed statistically significant associations and increased risk for AP presence in molars (odds ratio [OR] = 2.15; p < 0.001), teeth positioned in mandible (OR = 1.49; p = 0.007), teeth with short length of root filling (OR = 4.08; p < 0.001), overfilled teeth (OR = 2.99; p = 0.001), and teeth with inadequate density of root filling (OR = 4.14; p < 0.001). Considering variables related to coronal restoration, neither coronal restoration type nor quality was found to be predictive for posttreatment AP. Merely, the presence of intracanal post significantly increased the odds of AP presence (OR = 1.57; p = 0.009).Conclusion The results of the present study did not indicate that type or quality of coronal restoration may be predictors of posttreatment AP. Periapical disease was significantly associated with molars, mandibular teeth, substandard quality of root fillings, and intracanal post presence.
Keywords: dental; digital periapical radiograph; apical periodontitis; permanent coronal restoration; root canal treatment